2014
DOI: 10.1016/j.nlm.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Extinction, applied after retrieval of auditory fear memory, selectively increases zinc-finger protein 268 and phosphorylated ribosomal protein S6 expression in prefrontal cortex and lateral amygdala

Abstract: Retrieval of consolidated memories induces a labile phase during which memory can be disrupted or updated through a reconsolidation process. A central component of behavioral updating during reconsolidation using a retrieval-extinction manipulation (Ret+Ext) is the synaptic removal of a calcium-permeable-α-amino-3-hydroxyl-5-methyl-4-isoxazole-propionate receptor (CP-AMPARs) in the lateral amygdala-a metabotropic GluR1 receptor (mGluR1) dependent mechanism. In the present study, we investigate the effect of Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 30 publications
2
39
2
Order By: Relevance
“…The latter finding is significant in that it indicates a reversal of the synaptic changes that occurred during conditioning, supporting the view that the Monfils-Schiller paradigm results in unlearning of the original CS-US association. Furthermore, the Monfils-Schiller paradigm has been shown to induce neural modifications that are distinct from standard extinction (Lee et al, 2015; Tedesco et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…The latter finding is significant in that it indicates a reversal of the synaptic changes that occurred during conditioning, supporting the view that the Monfils-Schiller paradigm results in unlearning of the original CS-US association. Furthermore, the Monfils-Schiller paradigm has been shown to induce neural modifications that are distinct from standard extinction (Lee et al, 2015; Tedesco et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…We do not believe this could be the case. Recent studies have indeed shown that post-retrieval extinction engages mechanisms that are distinct from “standard” extinction (Monfils et al, 2009; Clem and Huganir, 2010; Rao-Ruiz et al, 2011; Tedesco et al, 2014; Lee et al, 2016). One explanation of memory updating is that an experience that both evokes a memory for and greatly resembles a previous experience (i.e., possess the same latent causes) is likely to be integrated with the previous memory.…”
Section: Discussionmentioning
confidence: 99%
“…For example, compared to conventional extinction, retrieval-extinction is associated with diminished involvement of the human ventromedial prefrontal cortex (vmPFC), as measured by functional neuroimaging, suggesting a potential disengagement of pathways associated with new inhibitory CS learning [80]. In contrast, increased expression of protein kinase M ζ (PKMζ) [78] and zinc-finger 268 (Zif268) in rodent vmPFC [84] is consistent with enhanced extinction of appetitive memory in this paradigm. Most interestingly, increased expression of phosphorylated ribosomal protein S6 (rpS6P) is specifically observed in both the lateral amygdala and mPFC after retrieval-extinction, but not extinction or retrieval alone (conditions equivalent to extinction and reconsolidation controls) [84].…”
Section: Discrimination On the Basis Of Biochemical Mechanismsmentioning
confidence: 99%
“…In contrast, increased expression of protein kinase M ζ (PKMζ) [78] and zinc-finger 268 (Zif268) in rodent vmPFC [84] is consistent with enhanced extinction of appetitive memory in this paradigm. Most interestingly, increased expression of phosphorylated ribosomal protein S6 (rpS6P) is specifically observed in both the lateral amygdala and mPFC after retrieval-extinction, but not extinction or retrieval alone (conditions equivalent to extinction and reconsolidation controls) [84]. Among the potential upstream regulators of rpS6P is metabotropic glutamate receptor 1 (mGlu1) [85], which has been independently implicated in both persistent threat memory attenuation and synaptic weakening after retrieval-extinction [21].…”
Section: Discrimination On the Basis Of Biochemical Mechanismsmentioning
confidence: 99%